The Relationship Between Physical Activity And Job Performance In Firefighters: A Systematıc Review - MUMCU, Neşe; CANİKLİ, Abdullah (Acta Scientiae et Intellectus, 2024)
This systematic review examines the relationship between physical activity and occupational performance in firefighters, a profession characterized by high physical and psychological demands. Drawing on 28 peer-reviewed studies published between 2000 and 2024, this paper evaluates how cardiorespiratory fitness, muscular strength, flexibility, and endurance contribute to task efficiency, injury prevention, and psychological resilience. Findings highlight that higher levels of physical fitness are associated with shorter response times, improved task execution under stress, and decreased incidence of musculoskeletal disorders. In addition, regular physical activity positively influences mental well-being by reducing fatigue, burnout, and post-traumatic stress symptoms. Studies also reveal the impact of institutional support, sleep quality, and ergonomic factors on sustaining firefighter health and performance. Overall, the evidence strongly supports implementing structured fitness and wellness programs tailored to the physical and psychological needs of emergency personnel. Promoting physical activity not only enhances immediate operational effectiveness but also ensures long-term occupational sustainability and resilience in high-risk professions.